2022
DOI: 10.1101/2022.05.29.493858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring light responses of primate retinal ganglion cells using intrinsic electrical signatures

Abstract: Reproducing high-acuity vision with an epiretinal implant will likely require inferring the natural light responses of diverse RGC types in the implanted retina, without measuring them directly. Here we demonstrate an approach that exploits intrinsic electrical features of primate RGCs. First, ON-parasol and OFF-parasol RGCs were identified with 95% accuracy using electrical features. Then, the somatic electrical footprint, predicted cell type, and average linear-nonlinear-Poisson model parameters of each cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…4D,E), as has been demonstrated previously in the peripheral retina (Fig. 4F,G, (Richard et al, 2016; Madugula et al, 2022a; Zaidi et al, 2022)). However, it is unclear how effective this method will be in a degenerated retina.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…4D,E), as has been demonstrated previously in the peripheral retina (Fig. 4F,G, (Richard et al, 2016; Madugula et al, 2022a; Zaidi et al, 2022)). However, it is unclear how effective this method will be in a degenerated retina.…”
Section: Discussionsupporting
confidence: 87%
“…Axon spike conduction velocity was estimated from the electrical images of ON and OFF parasol and midget cells, as described previously (Madugula et al, 2022a; Zaidi et al, 2022). Briefly, axonal electrodes for each cell were identified (see above) and pairwise velocity estimates were computed by dividing the distance between each electrode by the time difference in the negative peak amplitude, for each pair of axonal electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, new surgical methods must be developed to implant a tiny chip on the surface of the retina with stable contact. Second, receptive field locations, cell types and reconstruction filters must be inferred using electrical features rather than light-evoked responses in a blind retina (Sekirnjak et al 2011; Li et al 2015; Richard, Goetz, and Chichilnisky 2015; Zaidi et al 2022). Third, the stimulation approach must be modified to account for changes in spontaneous/oscillatory activity in the degenerated retina (Sekirnjak et al 2011; Goo et al 2015; Trenholm and Awatramani 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical implant, this would not be possible. Previous work has shown that distinct cell types can be identified from spontaneous electrical activity (Richard, Goetz, and Chichilnisky 2015; Zaidi et al 2022)…”
Section: Methodsmentioning
confidence: 99%